Kelestarian Budaya sebagai Dasar dalam Upaya Pengembangan Pariwisata di Yogyakarta - Hermawan Prasetyanto (Media Wisata, 2010)
Global Rivalry demands modernization existence at tourism sector. That thing necessary done so that tourist readies to pay a visit and felt to feet at home at city that visited. Conseqence from this modernization is builds amount of tourism sector supporting facilities. Troubleshoot appears when tourism sector development little by little threaten existence and local culture preservation. Inch by inch but certain society will adopted culture moderner that come from outside the culture self. That thing evoke problem aloof. Majority tourist comes to yogyakarta not in the first place to enjoy modern atmosphere, but exactly to know and enjoy atmosphere and local culture. If that looked for modern atmosphere, metropolis like Jakarta, Surabaya, and batam prepare it.so, if inch by inch local culture is shified, for certain that is long too long yogyakarta will lose asset to on the market in tourists. No more specification yogyakarta that can be putted to interesing tourist. Problem necessary looked for solusi , tourism development yogyakarta necessary aimed in torism development in culture preservation. To crat tourism development in culture preservation, there are some matter that can be goed. First. encouragement returns festival local culture. Second, necessary tourism planetology mapping existence. Third, give culture local load in special province Yogyakarta education curriculum. Fourth, revitalises the palace as a culture centre. Fifth, tourism development observer team formation. If success created tourism development that pays attention to culture preservation, can be believed that from time to time Yogyakarta permanent will can to defend its existence as a tourism city